The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3354/esr00560
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plant exudativory by the Bengal slow loris Nycticebus bengalensis

Abstract: Slow lorises are members of a rare guild of obligate exudativores. Secondary metabolites in their diet have been implicated as contributing to the evolution of both their slow basal metabolism and their venom. No long-term study has yet examined the feeding ecology of the largest of the lorises, the Bengal slow loris Nycticebus bengalensis. We conducted an 18 mo study from June 2008 to December 2010 in Hollongapar Gibbon Wildlife Sanctuary, Assam, India, to investigate whether Bengal slow lorises prefer gum, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Wild mango is a multipurpose tree species used for multiple purposes, including edible fruits, pickles, fodder, fuelwood, vegetable, plywood, tea chest and match boxes4142. A close genetic relationship between M. indica and M. sylvatica has been reported4344 which indicates that M. sylvatica may have the potential to fulfil nutritional and livelihood needs. It is underutilized in Bangladesh as well as in other tropical countries due to a lack of awareness of it’s potential as a source of food and no established market demand45.…”
Section: Discussionmentioning
confidence: 98%
“…Wild mango is a multipurpose tree species used for multiple purposes, including edible fruits, pickles, fodder, fuelwood, vegetable, plywood, tea chest and match boxes4142. A close genetic relationship between M. indica and M. sylvatica has been reported4344 which indicates that M. sylvatica may have the potential to fulfil nutritional and livelihood needs. It is underutilized in Bangladesh as well as in other tropical countries due to a lack of awareness of it’s potential as a source of food and no established market demand45.…”
Section: Discussionmentioning
confidence: 98%
“…All other studied slow loris species (studied in secondary or primary forests) also reported an exudate and insect based natural diet (Starr & Nekaris, 2013;Das et al, 2014;Wiens et al, 2006). All other studied slow loris species (studied in secondary or primary forests) also reported an exudate and insect based natural diet (Starr & Nekaris, 2013;Das et al, 2014;Wiens et al, 2006).…”
Section: Characterizing the Diet Of The Javan Slow Lorisesmentioning
confidence: 90%
“…Although originally suggested to be frugivorous based on comparisons with pottos (Charles-Dominique, 1977), wild field studies have clearly demonstrated that slow lorises (Nycticebus) are specialized exudativores (gum specialists) (Nekaris, 2014). The largest of the lorisines (1.1-2.4 kg), the Bengal slow loris (N. bengalensis) has been observed spending the majority of its feeding time on exudates (Pliosungnoen et al, 2010;Swapna et al, 2010), with only 4.45% time spent eating fruit (Das, Nekaris, & Bhattacharjee, 2014). The smaller bodied pygmy slow loris (N. pygmaeus) (350-550 g) has rarely been observed to ingest fruit in the wild, focusing on a diet of gum, nectar and insects (Starr & Nekaris, 2013;Streicher, 2009).…”
mentioning
confidence: 99%
“…Conducted crudely with wire cutters, nail clippers, or pliers, this procedure causes the death of many animals due to infection (Streicher et al 2008). Considering that the toothcomb is vital for defence, grooming, socialising with other lorises and, perhaps most importantly, gouging for gum (the most important element of a slow loris's diet) (Wiens et al 2006, Swapna et al 2010, Starr & Nekaris 2013, Streicher et al 2013, Das et al 2014, those that survive cannot be returned to the wild (Nekaris et al 2013b). …”
Section: Introductionmentioning
confidence: 99%